Threats posed to the fragile and pristine marine turtle (loggerhead & leatherback) eggs in the Maputaland coastline: a cross-sectional ecological assessment. - Mbanjwa, Sibonelo Thanda (Student’s Journal of Health Research Africa, 2026)
Background The Maputaland coastline in northern KwaZulu-Natal, South Africa, is a critical nesting habitat for the endangered Loggerhead (Caretta caretta) and Leatherback (Dermochelys coriacea) turtles. Despite its protected status, this region is increasingly exposed to anthropogenic pressures and environmental stressors that threaten turtle nesting success and egg survival. This study assessed key threats affecting marine turtle reproduction within the Maputaland Marine Protected Area (MPA). Methods A cross-sectional ecological assessment was conducted between November 2023 and March 2024, corresponding with the peak turtle nesting season. Data were collected along a 30 km stretch of coastline and included nest counts, hatchling success rates, records of physical disturbances (e.g., erosion and storm surges), observations of human activities (e.g., poaching, tourism, off-road vehicle tracks), and semi-structured interviews with conservation officers and local community members. Quantitative data were analysed using descriptive statistics, while qualitative data were analysed thematically. Results The overall hatchling success rate was 58%, with significantly lower success observed in areas experiencing high levels of human disturbance. Illegal poaching was responsible for 23% of recorded nest disturbances. Additional threats included artificial coastal lighting causing hatchling disorientation, dune erosion, and off-road vehicle activity. Qualitative findings revealed low public awareness of conservation legislation and the continued cultural consumption of turtle eggs. Conservation personnel highlighted limited patrol capacity and insufficient community outreach as major constraints to effective protection. Conclusion Both anthropogenic activities and natural stressors are undermining marine turtle reproductive success along the Maputaland coastline. Recommendations Community-based conservation approaches incorporating environmental education, strengthened enforcement of MPA regulations, turtle-friendly lighting, and sustainable eco-tourism practices are essential. Collaborative co-management involving local communities, conservation authorities, and academic institutions is critical for long-term turtle conservation and ecosystem resilience.